Implementation of Zero Run-Off (ZRO) system on Cocoa land to increase watershed performance. (February 2019) - Suhardi,; Munir, A; Sapsal, M T; Faridah, S N; Samsuar,
Abstract: One indicator of the decline in watershed performance is the increase in the ratio of maximum discharge to minimal discharge due to major surface runoff when rain occurs. Land use for cocoa cultivation can increase surface runoff by 389% compared to forest land. For this reason, it is necessary to implement a zero run-off system technology that can minimize surface runoff through increasing groundwater recharge. Groundwater recharge in the Zero runoff system (ZRO) was determined using Darcy's approach. This approach requires hydraulic gradient data obtained through measurements of groundwater levels around the ZRO system using two monitoring wells and hydraulic conductivity data of saturated soil. Groundwater levels are measured interactively using an aqua plumb liquid level sensor with data logger recording. The saturated hydraulic conductivity was determined using the falling head approach. Based on the result of the research, the hydraulic gradient in one of the ZRO system in the research location is 0.4, and the saturated hydraulic conductivity of 2.61 × 10 -5 m/s shows that the soil in the research location is moderately coarse or loamy textured. Thus, the velocity of water entering the subsurface is 1.04 × 10 -5 m/s, so that discharge of the groundwater recharge for one ZRO system is 4.16 × 10 -5 m 3 /s with the cross-sectional area of the ZRO system is 4 m 2